2022
DOI: 10.1002/jemt.24108
|View full text |Cite
|
Sign up to set email alerts
|

Implications of foliar epidermal micromorphology using light and scanning electron microscopy: A useful tool in taxonomy of Korean irises

Abstract: The genus Iris L., comprising approximately 210 species, is one of the most species-rich genera in the family Iridaceae. In this study, the first comprehensive leaf micromorphological characters of Korean irises were studied using light and scanning electron microscopy. Our objective was to evaluate the foliar micromorphological characteristics (namely epidermal cells, stomata types, and guard cell size) of Korean Iris taxa in a systematic context. All the investigated Korean Iris taxa had amphistomatic or hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 56 publications
2
13
0
Order By: Relevance
“…The micromorphological analysis performed in the present study revealed that I. ruthenica and I. uniflora possess leaves with an irregular shape and sinuate anticlinal striation, as previously reported 14 , 20 , 55 . Because both leaf surface micromorphology and stomata have shown considerable variation in papillae, they are not taxonomically significant, as suggested by Wu and Cutler 14 and other monocot species 56 , 57 .…”
Section: Discussionsupporting
confidence: 88%
“…The micromorphological analysis performed in the present study revealed that I. ruthenica and I. uniflora possess leaves with an irregular shape and sinuate anticlinal striation, as previously reported 14 , 20 , 55 . Because both leaf surface micromorphology and stomata have shown considerable variation in papillae, they are not taxonomically significant, as suggested by Wu and Cutler 14 and other monocot species 56 , 57 .…”
Section: Discussionsupporting
confidence: 88%
“…However, the pattern of leaf epidermal anticlinal cell wall can also be closely related to ecological condition as indicated in other plant groups (Moon et al, 2009; Stace, 1965). The surface ornamentation of leaves in this study revealed key diagnostic characters for the differentiation of Korean Ajuga species (Table 1) although, some traits like the pattern of epidermal pavement cells may be plastic, being closely related to ecological conditions such as xeric habitats or ecological conditions including high humidity (Choi, Ahn et al, 2022; Choi, Park et al, 2022; Kim et al, 2021; Kong & Hong, 2019; Stace, 1965; Stenglein et al, 2005). Likewise, amphistomatic leaves are commonly found in herbaceous species, but can also be a plastic trait associated with a xerophytic habitat (Parkhurst, 1978), or low light levels under which leaves differentiate (Muir, 2018).…”
Section: Discussionmentioning
confidence: 84%
“…We have previously characterized considerable genome size variation across Korean Ajuga species and have found that genome size is a useful taxonomic marker (Choi et al, 2019). It is still unknown whether micromorphological and cytological data correlate across the four Korean Ajuga species, as indicated in recent studies in other genera (Chen et al, 2022; Choi, Ahn et al, 2022; Choi, Park et al, 2022; Kim et al, 2021; Park et al, 2022).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Balcı, indicating that abnormal stomata were mainly determined by genetic factors and were secondarily affected by salinity. Abnormal stomatal patterning has been recorded in Brassicaceae, Asteraceae, Crassulaceae, Iridaceae, Leguminosae, Sonneratiaceae, and Moraceae (Gan et al, 2010;Khan et al, 2018;Choi et al, 2022). Abnormal stomata have been found in many plants grown in arid, salty, or otherwise adverse environments, similar abnormality was also detected in a halophyte, Sonneratia alba J. Smith (Gan et al, 2010;Khan et al, 2018).…”
Section: Black Sea Journal Of Agriculturementioning
confidence: 98%